Evaluation of RANS/actuator disk modelling of wind turbine wake flow using wind tunnel measurements. (1st January 2013) - Sumner, Jonathon; Espana, Guillaume; Masson, Christian; Aubrun, Sandrine
Wake modelling plays a central role in wind farm planning through the evaluation of losses, the prediction of the energy yield, and the estimation of turbine loads. These models must be reasonably accurate – to minimise financial risk – and yet economical so that many configurations can be tested within reasonable time. While many such models have been proposed, an especially attractive approach is based on the solution of the Reynolds-averaged Navier-Stokes equations with two-equation turbulence closure and an actuator disk representation of the rotor. The validity of this approach and its inherent limitations however remain to be fully understood. To this end, detailed wind tunnel measurements in the wake of a porous disk (with similar aerodynamic properties as a turbine rotor) immersed in a uniform flow are compared with the predictions of several closures. Agreement with measurements is found to be excellent for all models. This unexpected result seems to derive from a fundamental difference in the turbulent nature of the homogeneous wind tunnel flow and that of the atmospheric boundary layer.